Penerapan Shot List dan Story Line Sinematografi Pada Perancangan Video Animasi 3D Promosi SMA Negeri 4 Seluma - Cecep Saputra; Dandi Sunardi; Yuza Reswan; Yovi Apridiansyah (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2022)
The development of technology is currently developing so fast. Especially technology in the field of information and 3D animation. 3D animation is made with manual techniques to digital techniques. In making 3D animation, usually using software such as SketchUp, Blender, Unity and many other software. At this time 3D animation is used for many things, from making films, making video games, to the promotion of a certain building or agency, which aims to inform the general public about details, a shape or impression of the object. 3D animation has its own uniqueness which in the manufacturing process is not done by recording directly but through stages such as data collection, application of cinematographic techniques which include making storyboards, story objects, making shot lists.